Exploring Small and Medium Enterprises' Intention to Adopt AI - Powered Chatbots in Halal Marketing Communications - Nasution, Muhammad Dharma Tuah Putra; Rafiki, Ahmad; Rossanty, Yossie; Pahlufi, Cut Kesuma (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This study explores the adoption of AI chatbots in marketing communication by SMEs, specifically focusing on Halal contexts. It investigates factors such as perceived usefulness and attitude, which play a crucial role in shaping users' intentions. The mediating role of attitude, particularly in the context of Halal products, is significant, considering culturally sensitive considerations. The research adopts a quantitative approach with a correlational study design, utilizing random sampling to ensure representativeness. Data collection involves structured questionnaires, adapted scales, and 233 completed responses from SME owners/managers. Structural Equation Modeling (SEM) is employed for data analysis, testing complex relationships, and assessing direct and indirect impacts. The study reveals a positive direct effect of perceived usefulness and attitude toward chatbots (ATC) on chatbot adoption intention (CAI) in the Halal marketing context, supporting the hypothesis that both attitude and perceived usefulness significantly influence the intention to adopt AI chatbots. Additionally, the study explores the mediating role of attitude in the relationship between perceived usefulness and adoption intention. The findings contribute to existing literature by highlighting the complex interplay of factors influencing users' attitudes and intentions towards AI chatbots in marketing communication, particularly in the Halal context.